Corporate Governance Quality and Audit Quality in Malaysia - Kee, Ho Wai; Hock, Oo Yu; Kueng, Kwong Chee (2017)
This paper examines the impact of corporate governance quality on audit quality in Malaysia. The sampling frame is 457 Malaysian non-finance listed companies, over the periods 2003 to 2007 (pre-2007 Code period) and 2008 to 2012 (post -2007 Code period), consisting of 2,285 observations for each period. This study uses pooled ordinary least square (OLS) to test the research hypotheses and model. The results show that the effectiveness of the audit committee (AC) has no significant influence on audit fees in the pre- and post-2007 Code period, and the effectiveness of the board has no significant influence on audit fees in the pre-2007 Code period, although it has significant influence on audit fees in the post-2007 Code period. The results suggest that the existing corporate governance framework in relation to AC has limitation in its governance role on audit process. Our study contributes to existing literature conducted in the US, the UK and Australia where their institutional settings are different from that of Malaysia. In addition, our study is based on the 2007 Code’s recommendation which contributes to the previous research conducted in Malaysia and provides an insightful evidence to the regulator on the corporate governance regime in Malaysia.